How Long Does it Take to Initiate a Child on Long-Term Invasive Ventilation? Results From A Canadian Pediatric Home Ventilation Program - Reshma Amin; Aarti Sayal; Faiza Syed; Cathy Daniels; Andrea Hoffman; Theo J Moraes; Peter Cox (Canadian Respiratory Journal)
OBJECTIVE: To assess the length of stay required to initiate long-term invasive ventilation at the authors’ institution, which would inform future interventional strategies to streamline the in-hospital stay for these families.